Domestic Historiography of Stay of Japanese Prisoners of War on Territory of Khakassia in 1945-1947 - S. V. Serebrennikov (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The domestic historiography of stay of Japanese prisoners of war in the territory of Khakass Autonomous region in 1945-1947 is considered for the first time. The article contains a historiographical analysis of the works of Russian historians, published in the period from 1994 to 2016, which addresses the issues of stay of Japanese prisoners of war on the territory of Khakassia. The author noted the lack of scholarly monographs on Japanese prisoners placed in the Khakass Autonomous region after the second world war. Information on the presence of Japanese prisoners of war in the region contained in the few publications on Japanese prisoners, located in the Krasnoyarsk region, and a number of historians of foreign prisoners of war of the second world war in Siberia is identified and analyzed. Insufficient knowledge of a number of questions of stay of Japanese prisoners of war on the territory of Khakassia is stated. Historical publications about the Japanese prisoners, located in Krasnoyarsk Region, obviously pay the authors’ attention to the study of Japanese prisoners of war camp No. 34, which office and camp departments were located outside of the Republic of Khakassia. Significantly less attention is paid to the Khakass camp No. 33. The greatest contribution to the study of different aspects of stay of Japanese prisoners of war on the territory of Khakass Autonomous region in the years 1945-1947 made Krasnoyarsk historian M. N. Spiridonov. But after the publication of the monograph dedicated to the Japanese prisoners of war located in Krasnoyarsk Region (2003), he did not publish no single work on the subject. The author believes that, in addition to more in-depth study of some insufficiently studied questions of the topic, it is advisable to prepare and publish a collection of papers on various aspects of stay of Japanese prisoners of war on the territory of Khakassia.